Meningkatkan keaktifan dan hasil belajar IPA siswa kelas VI SDN 02 Krompeng melalui pembelajaran Think – Pair – Share - Rini Hartatik (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This research is an effort to increase the activeness and learning outcomes of sixth grade students at SDN 02 Krompeng, Talun, Pekalongan Regency. This type of research is classroom action research. The research model used is Kurt Lewin using two cycles. The subjects in this study were students of class SDN 02 Krompeng, Talun, Pekalongan Regency, totaling 24 students. The data collection method used in this research is the test method and the observation method. While the data collection instrument used was an observation format for the implementation of TPS model cooperative learning by the teacher, the observation format for student activities/activities in the implementation of the TPS cooperative learning stages by students included a cooperative observation sheet and student activity. The data analysis technique was carried out in a qualitative descriptive manner. Indicators of student success are marked by increased activity and learning outcomes with student mastery reaching 80%. The results of this study indicate that the use of the Think Pair Share (TPS) learning model can increase the activeness and learning outcomes of science subjects at SDN 02 Krompeng, Talun, Pekalongan Regency. The results showed that TPS type cooperative learning can improve student learning outcomes as indicated by an increase in the number of students who completed learning as many as 16 students in the first cycle to 21 students in the second cycle, and the percentage of classical learning completeness increased from 66.67% in the first cycle to 87.5% in cycle II. Thus, students complete learning both classically and individually. Meanwhile, the implementation of TPS type cooperative learning by teachers also increased from cycle I to cycle II, namely from 68% to 85% with an increase of 17%. This indicates that the teacher has been able to carry out learning using the TPS model well. Student cooperation increased from 60% in the first cycle to 77% in the second cycle, besides that student activity also increased from 68.8% in the first cycle to 87.5% in the second cycle with an increase of 18.7%. This can indicate that students have understood and can carry out the stages of cooperative learning with the TPS model well. Based on the results, this study has reached the indicators of success, and it can be concluded that the TPS type cooperative learning model can improve student learning outcomes and increase activeness in science learning.